MODEL MATEMATIKA SIR PADA PENYEBARAN PENYAKIT COVID-19 DENGAN EFEKTIVITAS VAKSIN - ARMITA, NI LUH GEDE SHINDYA; HARINI, LUH PUTU IDA; UTARI, IDA AYU PUTU ARI (E-Jurnal Matematika; Vol 13 No 1 (2024)DO - 10.24843/MTK.2024.v13.i01.p439, 2024)
Corona Virus Disease (COVID-19) is one of the disease outbreaks that has spread throughout the world since the end of 2019. This disease causes infected individuals to experience infections in the respiratory tract with a fairly high risk. One branch of mathematics that can help overcome this case is the formation of mathematical models. The model formed is the SIR model basically describes the spread of disease in the Susceptible (S), Infected (I), Recovered (R) classes, but in this study the Infected (I) class was classified into two and added parameters to decrease vaccine effectiveness. The former model is then used to find a solution in the form of a disease-free equilibrium point, where the point will be used to form a basic reproduction number. To prove that the equilibrium point found to be stable, a stability analysis will be carried out and in the model that has been formed it is found that the disease-free equilibrium point is locally asymptotic stable with the condition that. After analysis, it was found that the rate of decline in vaccine effectiveness was quite influential on the class of infection .